How will the Legal Battle End in the Public Job : Sight of Jordan Issue - Mohammed Abdul Mohsen Mohammed bin Treef; Ibtsam Alsaleh; Kamal Mohamoud Alasaf; Hiba Abdulmyuttaleb Alfadhlei (Faculty of Law, Universitas Sebelas Maret, 2022)
Conflict of interests, as an act of corruption, is considered a loose concept. Legal jurisprudence differed in defining its concept, but the salient feature in it is that it constitutes an act of a public job that calls for both disciplinary and criminal responsibility, as it constitutes a two-faced act, a criminal and a disciplinary aspect. This study came to examine a important issue within the framework of the public job. From here it was necessary to stand on the definition of conflict of interest and the types of this conflict within the framework of the public job, and the elements of the crime of conflict of interest according to the criminal framework in the punitive legislation in the countries under study. The main findings show that the most prominent of which is that the most common and dangerous form of conflict is the conflict between the public interest and the private interest. This is when the employee has a direct or indirect interest that affects the administrative decision-making process or any other administrative act. The two researchers recommended that more details be given to the images of Conflict of interests in order to avoid any legal lapse or loophole, which would result in the establishment of the largest possible criminal and disciplinary confrontation for this act.